Mixed cell computation in Hom4PS-3. (March 2017) - Chen, Tianran; Lee, Tsung-Lin; Li, Tien-Yien
Abstract: This article presents recent efforts in improving the efficiency and scalability of the mixed cell computation step in the context of the Polyhedral Homotopy method. Solving systems of polynomial equations is an important problem in applied mathematics. The Polyhedral Homotopy method is an important numerical method for this task. In this method, a necessary preprocessing step, known as the "mixed cell computation" problem has been the main bottleneck in the parallel efficiency and scalability. This article presents recent remarkable improvements in the parallel scalability of the algorithm that are applicable to a wide range of hardware architectures including multi-core systems, NUMA systems, computer clusters, and GPUs devices.